Original papersBalancing between bleeding and thromboembolism after percutaneous coronary intervention in patients with atrial fibrillation. Could triple anticoagulant therapy be a solution? - Dąbrowska, Magdalena; Ochała, Andrzej; Cybulski, Wiesław; Tendera, Michał (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : Atrial fibrillation (AF) has nowadays become a common disease as it comes along with medical procedures propagation in the ageing population with coexistent diseases. Hence a need for use of combined anticoagulant and antithrombotic therapy has arisen. According to the 2010 ESC guidelines on myocardial revascularization, short-term triple antithrombotic therapy after percutaneous coronary intervention (PCI) should be given if compelling indications exist. Aim: To assess bleeding and thromboembolic events depending on the antithrombotic regimen in short- and long-term follow-up in patients with AF after PCI with stent implantation. Material and methods : A 12-month prospective, non-randomized registry was conducted in the 3rd Department of Cardiology in the Upper Silesian Medical Center in Katowice from October 2008 to April 2011. One hundred and four patients in two groups – on triple therapy (TT; aspirin + clopidogrel + vitamin K antagonists (VKA; warfarin or acenocoumarol) n = 44) and on dual therapy (DT; aspirin + clopidogrel; n = 60) – were assessed 30 days and 12 months after angioplasty. Results: All bleeding events occurred more often in the triple anticoagulated group in 30 days (TT 20.5% vs. DT 6.7%; p = 0.03) and after 12 months (TT 38.9% vs. DT 17.2%, p = 0.09). The difference in major bleeding events was not significant after 30 days (TT 9.1% vs. DT 3.3%; p = NS) or 12 months (TT 11.1% vs. DT 6.9%; p = NS). Thromboembolic events after 30 days (DT 5.0% vs. TT 2.3%) and 12 months (TT 11.1% vs. DT 3.4%) were comparable. The percentage of deaths after 30 days (DT 1.7% vs. TT 0.0%, p = NS) increased after 12 months (DT 13.8% vs. TT 0.0%, p = 0.09). Conclusions : Significantly higher risk of bleeding on TT becomes blurred by a tendency to increased mortality in patients on DT.